Hankel wavelet multiplier associated with the unitary representation - Shukla P.; Upadhyay S.K. (My University, 2025)
In this paper, the boundedness and compactness of the Hankel wavelet multiplier associated with the unitary representation on Lp space for 1 ≤ p ≤∞, are obtained by using the Hankel transform technique. The application of Hankel wavelet multipliers in form of the Landau-Pollak-Slepian operator is given. With the help of the Hankel wavelet multiplier, the Sobolev space associated with the Hankel transform is constructed and its various properties are studied. © 2025 World Scientific Publishing Company.